Poet writes herself out of grief - Douman, Bronwyn (WritingThreeSixty, 2018)
WritingThreeSixty attended the book launch of I Am The Rose by poet, artist, and feminist scholar Zulfa Abrahams on Tuesday the 2nd of December 2014 at the Artscape Opera Bar.